2018
DOI: 10.1007/s10826-018-1078-4
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Bullying Experiences, Adolescent Behavioral and Mental Health, and Academic Achievement: An Integrative Model of Perpetration, Victimization, and Bystander Behavior

Abstract: Bullying is often ongoing during middle- and high-school. However, limited research has examined how cumulative experiences of victimization, perpetration, and bystander behavior impact adolescent behavioral and mental health and academic achievement outcomes at the end of high school. The current study used a sample of over 8000 middle- and high-school students (51% female; mean age 12.5 years) from the Rural Adaptation Project in North Carolina to investigate how cumulative experiences as a bullying victim a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 50 publications
(59 reference statements)
8
43
2
1
Order By: Relevance
“…As hypothesized, being a bystander of cyberbullying was related positively to adolescents' self-report of depression and anxiety, measured one year later (Hypothesis 1). This result is consistent with previous research on bystanders of offline bullying (Evans et al, 2018;Rivers et al, 2009) and more broadly, with research on cyberbullying perpetration and victimization (Bauman et al, 2013;Bonanno et al, 2013;Mitchell et al, 2007;Wright, 2014;Ybarra et al, 2007;Yousef & Bellamy, 2015). This finding extends the current literature on the consequences of witnessing cyberbullying for bystanders.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As hypothesized, being a bystander of cyberbullying was related positively to adolescents' self-report of depression and anxiety, measured one year later (Hypothesis 1). This result is consistent with previous research on bystanders of offline bullying (Evans et al, 2018;Rivers et al, 2009) and more broadly, with research on cyberbullying perpetration and victimization (Bauman et al, 2013;Bonanno et al, 2013;Mitchell et al, 2007;Wright, 2014;Ybarra et al, 2007;Yousef & Bellamy, 2015). This finding extends the current literature on the consequences of witnessing cyberbullying for bystanders.…”
Section: Discussionsupporting
confidence: 91%
“…Research on offline bullying provides a foundation for understanding the negative consequences of witnessing cyberbullying. In the research on offline bullying, Evans, Smokowski, Rose, Mercado, and Marshall (2018) found that negative bystander behavior (e.g., not intervening in bullying incidences) was associated positively with anxiety, depression, and academic difficulties among adolescents. Similar results were found by Rivers and colleagues (2009), regardless of whether adolescents were also directly involved in offline bullying behavior or victimization.…”
Section: Cyberbullying Depression and Anxietymentioning
confidence: 99%
“…Bullying victimization, that is both "face to face", and through the ICT, includes a wide range of serious short-term and long-term mental health problems [14][15][16][17][18][19][20][21]. A quasi-experimental meta-analytical study showed how bullying victimization generates behavioral and emotional problems as symptoms of their psychological distress in response to the bullying experience, including internalizing symptoms such as anxiety, depression and suicidality [22].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, each differing in combinations of bias-based bullying, demonstrate that experiencing multiple forms of bias-based bullying is harmful for mental health (Garnett et al 2014;Shramko et al 2018). While longterm health correlates of overlapping forms of bias-based bullying have not yet been investigated, research in related areas demonstrates that multiple types of victimization in multiple contexts (e.g., home, school, and community) and multiple forms of general bullying not based on bias are particularly harmful to healthy development (Evans et al 2014(Evans et al , 2018Turner et al 2016). Future work with LGBQ youth investigating these associations with multiple forms of bias-based bullying are needed to elaborate our understanding of the implications of these overlapping forms of bias.…”
Section: Discussionmentioning
confidence: 99%